Effects of trees distribution in soil attributes in shaded coffee - Morinigo, Kátia Priscilla Gomes; Guimarães, Nathalia de França; Stolf, Rubismar; Sais, Adriana Cavalieri; Souza, Maicon Douglas Bispo de; Gallo, Anderson de Souza; Fontanetti, Anastácia (Coffee Science - ISSN 1984-3909, 2017)
The objective in this work was to evaluate the effect of spatial distribution of tree species (Anadenanthera falcata, Albizia polycephala e Cassia grandis) on shaded coffee plants (Coffea arabica cv. Obatâ), to mechanical strength, moisture and chemical characteristics of the soil. The experimental design was randomized block with four replicates in a 4x2 factorial scheme. The first factor the location of soil sampling on the shaded coffee plantation, determined by two points in the trees planting rows (D1L distancing one meter from the tree trunk and D6L distancing six meters from the tree trunks) and two point, parallel to those, in the inter row (D1E and D6E). The second factor was the soil sampling depth: 0.00-0.20 and 0.20-0.40 meters. The soil largest mechanical resistances were found in D1L and D1E, with 8.889 Mpa and 6.55 Mpa, respectively. The soil lowest pH values (4.62) and greatest aluminum contents (4.95 mmolc dm-3) were found in the trees planting rows at D1L. Trees spatial distribution did not affected soil moisture, that varied from 0.11 to 0.14 kg kg-1 or soils contents of organic matter as well as sums of phosphor, potassium, calcium or magnesium, that were within proper level to coffee plants cropping. In conclusion, the evaluated trees raised soil resistance to penetration and probable exert great competition for nutrients with the coffee trees, increasing soil pH values and aluminum contents, when located at D1L, possibly, due roots distribution and concentration of these tree species. However, trees distribution did not affected soil moisture, its organic matter contents or P, K and Ca sums.